2019 57th Annual Allerton Conference on Communication, Control, and Computing (Allerton) 2019
DOI: 10.1109/allerton.2019.8919803
|View full text |Cite
|
Sign up to set email alerts
|

Local Distribution Obfuscation via Probability Coupling

Abstract: We introduce a general model for the local obfuscation of probability distributions by probabilistic perturbation, e.g., by adding differentially private noise, and investigate its theoretical properties. Specifically, we relax a notion of distribution privacy (DistP) by generalizing it to divergence, and propose local obfuscation mechanisms that provide divergence distribution privacy. To provide f -divergence distribution privacy, we prove that probabilistic perturbation noise should be added proportionally … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In [28], the authors used Laplace distribution and showed that by temporally smoothing the aggregated data, a group size of the order of thousands of SMs is sufficient for estimation of aggregated consumption. The authors in [29] introduced a model for local obfuscation of probability distribution by probability perturbation, which perturbed each single "point" datum by adding controlled probabilistic noise before sending it out to a data collector. The authors in [30] studied noise addition as a data privacy providing technique.…”
Section: A Additivementioning
confidence: 99%
“…In [28], the authors used Laplace distribution and showed that by temporally smoothing the aggregated data, a group size of the order of thousands of SMs is sufficient for estimation of aggregated consumption. The authors in [29] introduced a model for local obfuscation of probability distribution by probability perturbation, which perturbed each single "point" datum by adding controlled probabilistic noise before sending it out to a data collector. The authors in [30] studied noise addition as a data privacy providing technique.…”
Section: A Additivementioning
confidence: 99%
“…Indeed, many definitions mentioned in this section were actually introduced with a δ parameter allowing for a small probability of error. One particularly general example is adjacency relation divergence DP [97], which combines an arbitrary neighborhood definition (like in generic DP) with an arbitrary divergence function (like in divergence DP).…”
Section: Multidimensional Definitionsmentioning
confidence: 99%
“…For example, in [107], the author proposes endogeneous DP, which is a combination of (ε, δ)-DP and personalized DP. Similarly, pseudo-metric DP, defined in [36], is a combination of d D -privacy and (ε, δ)-DP; while extended divergence DP [97] combines d D -privacy with divergence DP.…”
Section: Multidimensional Definitionsmentioning
confidence: 99%
See 2 more Smart Citations